2019
DOI: 10.1590/1516-4446-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Component mechanisms of executive function in schizophrenia and their contribution to functional outcomes

Abstract: Objective:In schizophrenia, scores reflecting deficits in different cognitive processes are strongly correlated, making it difficult to establish a solid relationship between different cognitive mechanisms and other features of this disorder. The objective of this study was to explore whether three frequently postulated executive functions (updating, shifting, and inhibition) could be compared between groups and considered independently in terms of their respective roles in functional outcome.Methods:This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, according to Friedman and Miyake (6), executive functions represent a set of control processes that regulate thoughts and behavior, dysfunctions in which are symptomatic of neuropsychiatric and behavioral disorders. Although there is some debate over which variables should be used to assess executive functioning, inhibitory control, working memory, decision-making, cognitive flexibility, planning, problemsolving are generally well established in neurocognitive research (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Friedman and Miyake (6), executive functions represent a set of control processes that regulate thoughts and behavior, dysfunctions in which are symptomatic of neuropsychiatric and behavioral disorders. Although there is some debate over which variables should be used to assess executive functioning, inhibitory control, working memory, decision-making, cognitive flexibility, planning, problemsolving are generally well established in neurocognitive research (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…An executive impairment, more specifically one in inhibition/attention, in FM patients could relate to their clinical management, since these skills are associated with different outcomes in clinical and healthy populations, including adherence to treatment (Alosco et al, 2012; Dominguez-Salas et al, 2016; Huerta et al, 2016; Kosilov et al, 2020), resilience, quality of life, and functionality (Berberian et al, 2019; Davis et al, 2010; Parsons et al, 2016). Inhibition seems to be a first and fundamental step to any self-regulated behavior (Baumeister, 2014), as it involves the selection of relevant information, the control of inappropriate responses, and the interruption of overbearing or habitual responses so that one can then engage in organization, planning and behavior change (Baggetta & Alexander, 2016; Diamond, 2013; Friedman & Miyake, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating EF in these patients may be relevant because these skills are associated with outcomes of clinical relevance, such as adherence to treatment in patients with different diagnoses (Alosco et al, 2012; Dominguez-Salas et al, 2016; Huerta et al, 2016; Kosilov et al, 2020). Furthermore, EF have also been associated with resilience, quality of life, and functionality (Berberian et al, 2019; Davis et al, 2010; Parsons et al, 2016) in different healthy and clinical populations. These findings suggest that considering EF in FM research and the clinical practice may be relevant from the perspective of patient care.…”
mentioning
confidence: 99%
“…Although all functioning domains are affected in this population, the degree of differentiated involvement by domains is very notable, we find levels of severe disability (values of more than 50 % disability), in the domains of participation in society and interpersonal getting along (relationship), which have a logic with the way of presentation and evolution of mental disorders, especially in those considered serious as schizophrenia and other primary psychotic disorders [16], in which we observe a decrease in social functioning much earlier than symptomatic appearance, mainly the one that demands social interaction. We also found moderate disability (those domains with disability levels between 25 and 49%), in the domain of cognition and activities at home; regarding these observed data, we know that mental disorders are the cause of various cognitive dysfunctions (abilities to pay attention, remember, process information, solve problems, organize and reorganize information, communicate and react to received information) and are often the primary symptom in psychotic disorders [17], for example in the schizophrenia the executive functions components have been associated with the general measure of functional outcome, by the way, studies have suggested that cognitive task performance can be broken down into the same broad domains in both schizophrenic and other populations (like healthy population) [18].…”
Section: Discussionmentioning
confidence: 99%